2022
DOI: 10.1007/s10237-022-01563-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inlet flow profile and nozzle diameter on drug delivery to the maxillary sinus

Abstract: In this paper, the effect of the turbulence and swirling of the inlet flow and the diameter of the nozzle on the flow characteristics and the particles' transport/deposition patterns in a realistic combination of the nasal cavity (NC) and the maxillary sinus (MS) were examined. A computational fluid dynamics (CFD) model was developed in ANSYS® Fluent using a hybrid Reynolds averaged Navier–Stokes–large-eddy simulation algorithm. For the validation of the CFD model, the pressure distribution in the NC was compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The physical principle is to increase the transfer of airborne droplets from the nasal cavity to the sinus cavity through the oscillatory exchange of air across the maxillary ostium according to the Helmholtz resonator theory ( Figure 1 ). This oscillating airflow resulting from the acoustic wave allows a pressure gradient to be generated between the nasal fossae and the sinus cavity, which is a poorly ventilated area [ 11 , 12 , 13 ]. Thus, it has been previously demonstrated that the superposition of an acoustic wave on the airborne droplets produced by a nebulizer can allow, in some cases, a significant improvement of intrasinus drug deposition [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The physical principle is to increase the transfer of airborne droplets from the nasal cavity to the sinus cavity through the oscillatory exchange of air across the maxillary ostium according to the Helmholtz resonator theory ( Figure 1 ). This oscillating airflow resulting from the acoustic wave allows a pressure gradient to be generated between the nasal fossae and the sinus cavity, which is a poorly ventilated area [ 11 , 12 , 13 ]. Thus, it has been previously demonstrated that the superposition of an acoustic wave on the airborne droplets produced by a nebulizer can allow, in some cases, a significant improvement of intrasinus drug deposition [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Optimised mechanical properties lead to the smooth and robust integration of biomaterials into target tissues, reducing inflammation and enhancing the efficacy of the artificial organ or scaffold [5,7]. In drug delivery systems, acoustic analysis and fluid flow studies help researchers and clinicians gain a better understanding of therapeutic particle motion and improve drug delivery rates [8,9]. Moreover, biomechanical features are used as indicators of disease for detection purposes and in treatment monitoring to assess therapy effectiveness [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…25 In the Computational Fluid Dynamics (CFD) domain, wall behaviour is considered rigid in all types of mathematical modelling. [26][27][28][29] Therefore, the application of CFD methods to represent human body organs with viscoelastic behaviour creates an aura of ambiguity. The Fluid-Structure Interaction (FSI) method has been used to solve this problem, such that wall properties are considered in the mathematical model of the organ.…”
Section: Introductionmentioning
confidence: 99%